Becoming-world: Deleuze, virtual reality, and the ethics of narrative immersion - Amlashi, Emad Abouata; Adiloglu, Fatos (Sage Publications Inc, 2025)
This article examines how Deleuzean philosophy can inform the design and analysis of Virtual Reality (VR) narratives, focusing on the concepts of becoming, assemblage, and immanence. The research addresses the question: How can VR narratives foster ethical reflection and participant engagement, particularly on issues of social justice and representation? Through a post-qualitative methodology and narrative analysis of four VR films - 'Notes on Blindness', 'Clouds Over Sidra', 'The Key', and 'Giant' - the study demonstrates how VR enables participants to engage in processes of becoming-other, provoking sensory and emotional transformations. These films illustrate how VR narratives allow for co-creation, ethical reflection, and empathy by immersing participants in complex ethical dilemmas related to disability, trauma, and displacement. Based on these findings, the article proposes an ethical framework for VR narrative design, emphasizing participant agency, immanent ethics, and the integration of social justice themes.
Keywords: Becoming; Deleuzean philosophy; ethical reflection; narrative design; social justice; virtual reality